A Novel Cut-out Syringe Scalp Retractor for Endoscopic Strip Craniectomy for Craniosynostosis—A Cost-effective and Durable Alternative - Mittal, Amol; Mishra, Rakesh; Chegondi, Ranjith; Patel, Hrishikesh J.; Shrivastava, Adesh (Asian Journal of Neurosurgery, 2025)
Unilateral coronal craniosynostosis is the second most common subtype of nonsyndromic craniosynostosis. Endoscopic repair requires a scalp and dural retractor for adequate visualization and performing strip craniectomy. We describe the application of a novel cut-out syringe scalp retractor for endoscopic repair of unilateral coronal craniosynostosis.A 3-month-old female child presented with a progressive abnormal head shape. Three-dimensional reconstruction of brain CT showed a right fused coronal suture with ipsilateral temporal and contralateral frontal prominence. A diagnosis of unilateral coronal synostosis was made. The patient underwent endoscopic strip craniectomy using a novel cut-out syringe scalp retractor. The craniectomy extended from the right squamosal suture to the anterior fontanelle. The postoperative recovery was uneventful.The main aim of endoscopic surgery is to swiftly address the progression of calvarial and facial dysmorphism. The timings of endoscopic repair are crucial and usually performed before 3 months of age. It has a distinct advantage over open repair owing to shorter hospital stays, less bleeding, lower operative times, comparable aesthetic outcomes, and being minimally invasive. For endoscopic repair, various retractors have been described in the literature but these retractors are difficult to procure in resource-constrained setup. We advocate the usage of a cost-effective, durable, reusable, and malleable scalp retractor whose cost is nominal. It can be safely sterilized or can be newly made for every case. We found this retractor to be extremely useful in the case of endoscopic strip craniectomy.
Keywords: coronal craniosynostosis; endoscopic repair; syringe retractor; novel technique; strip craniectomy